Redeeming Lost Mothers: Adolescent Antiretroviral Treatment and the Making of Home in South Africa. Issue 6 (1st November 2016) - Vale, Beth; Thabeng, Mildred
ABSTRACT: In this article, we explore how adolescent antiretroviral treatment (ART) might be signified to repair sociality in Eastern Cape homes that have been ruptured by HIV/AIDS and maternal loss. The post-apartheid period has exposed these families to new forms of social fragmentation, propelled by the disintegration of wage labor, declining marriage rates, and a rampant HIV/AIDS epidemic. Drawing on eight months of ethnographic fieldwork (August 2013–April 2014), we show that in the homes of some adolescents born with HIV, these present-day domestic ruptures were discursively connected to the past shortcomings of their dead and absent mothers. In some familial narratives lost mothers were accused of disobeying their elders, neglecting their children, and flouting custom; their social transgressions were made manifest in their child's inherited HIV. By signifying adolescent ART-taking as an enactment of the discipline and care purportedly absent in their mothers, these families might also attempt to imbue ART, beyond its biomedical function, as a means of social repair.